High-Elevation Monsoon Precipitation Processes in the Central Andes of Peru - Chavez, S. P. (2020)
Measurements at the high-elevation Lamar Observatory in the Mantaro Valley (MV) in the Central Andes of Peru demonstrate a diurnal cycle of precipitation characterized by convective rainfall during the afternoon and nighttime stratiform rainfall with embedded convection. Wet season data (2016-2018) reveal long-duration (6-12 hr) shallow precipitating systems (LDPS) that produced about 17% of monsoon rainfall in 2016 and 2018 associated with El Nino and La Nina, respectively. The LPDS fraction of monsoon rainfall doubles to 35% with weekly recurrence in 2017 under El Nino Costero (coastal) conditions. LDPS occur under favorable moisture conditions dictated by the South America (SA) Low-Level Jet (SALLJ) and Cold Air Intrusions (CAIs). Backward trajectory analysis shows that precipitable water sustains >80% of seasonal precipitation and ties the LPDS to particular moisture source regions in the eastern Andes foothills 1-2 days in advance, enhanced by increased moisture supply in the midtroposphere. Higher frequency of CAIs and enhanced midlevel moisture convergence along CAI fronts explain the increased LDPS frequency during the 2017 El Nino Costero. These findings highlight the functional role of the Andes morphology in organizing moisture supply to high-elevation precipitation systems on the orographic envelope. Analysis of the Global Precipitation Measurement (GPM) mission satellite-based radar observations points to challenges to precipitation detection and estimation in this region as the GPM clutter-free height (similar to 1-2 km AGL) exceeds the depth of shallow precipitation systems in the MV.